Efeito estabilizante de montmorilonita sobre antocianinas de acerola: aplicação em suco clarificado e filmes comestíveis - Ribeiro, Hálisson Lucas (2016)
Anthocyanins are the most widely distributed flavonoids in plants, being responsible for colors ranging from blue to red-orange. The anthocyanins from acerolas (Malpighia emarginata DC) are very prone to degradation upon processing and storage, resulting in changes in their characateristic red color to a yellowish or brownish color((DE ROSSO; MERCADANTE, 2007), decreasing the commercial appeal of the final products. Thus, it is important to use techniques to stabilize anthocyanins in acerola products. Anthocyanin stability may be improved by copigmentation, in which the pigment and a second compound (copigment, organic or inorganic) form molecular associations which promote color intensification and/or stabilization. The use of nanoadsorbents for copigmentation has been studied recently. Among those, the montmorillonite-type clays (MMT) should be mentioned, whose effects on anthocyanin stabilization have been reported. MMT is commonly used as a reinforcement phase for polymeric materials, improving their mechanical and barrier properties. The objective of the present study was to evaluate the anthocyanin stabilization by MMT on acerola clarified juice and edible gelatin films containing acerola juice. The MMT addition promoted complexation of anthocyanins in acerola juice, with concomitant intensification of the red color and stabilization of the color parameters as functions of pH and storage time. Mass spectrometry indicated anthocyanin adsorption by MMT. The addition of 6.4% MMT (on a gelatin weight basis) to the films resulted in 30% increasing on tensile strength and 44% decreasing on water vapor permeability. Moreover, MMT promoted reduction in color lightness (L*) and intensification in red color.